2022
DOI: 10.1186/s12933-022-01683-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between the triglyceride-glucose index and carotid plaque incidence: a longitudinal study

Abstract: Background Carotid plaque and triglyceride-glucose (TyG) index are associated with insulin resistance. However, a highly debated question is whether there is an association between the TyG index and carotid plaque incidence. Thus we performed an in-depth longitudinal study to investigate the relationship between carotid plaque occurrence and the TyG index among Chinese individuals. Methods Two thousand and three hundred seventy subjects (1381 males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 47 publications
0
10
1
Order By: Relevance
“…Previous studies have found strongly correlation between TyG index, TyG-BMI index and TG/HDL-C ratio and mortality in different populations. In a recent large cross-sectional study, TyG-BMI was found to be associated with CVD mortality among participants from the National Health and Nutrition Examination Survey (NHANES), and ROC analysis showed that the TyG index had better predictive ability for CVD mortality than the TyG-BMI index [21]. Similarly, in a large prospective cohort study, Lopez-Jaramillo et al reveled the positive correlation between higher TyG index and cardiovascular mortality [22].…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have found strongly correlation between TyG index, TyG-BMI index and TG/HDL-C ratio and mortality in different populations. In a recent large cross-sectional study, TyG-BMI was found to be associated with CVD mortality among participants from the National Health and Nutrition Examination Survey (NHANES), and ROC analysis showed that the TyG index had better predictive ability for CVD mortality than the TyG-BMI index [21]. Similarly, in a large prospective cohort study, Lopez-Jaramillo et al reveled the positive correlation between higher TyG index and cardiovascular mortality [22].…”
Section: Discussionmentioning
confidence: 95%
“…Additionally, the final multivariate logistic regression equation excluded BG and TG as the confounding variables as they consist of the TyG Index. Whether the confounding variables were adjusted was determined by the following principle: Based on its association with the outcomes of interest, clinical significance, reports in the literature and changed the matched OR by at least 10%16 17 19(online supplemental table 1).…”
Section: Methodsmentioning
confidence: 99%
“…A study of urban workers in China reported that a higher TyG Index increased the risk of carotid plaque 16. Three studies have also reported a positive association between the TyG Index and carotid plaque based on prospective cohort designs in China 17–19. By contrast, another community-based observational research in a Chinese non-diabetic population observed the significantly positive relationship of TyG Index with carotid plaque instability, but did not find a statistically significant relationship between the TyG Index level and stable carotid plaque 20.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ratio of triglycerides to high-density lipoprotein cholesterol (TG/HDL-C), triglyceride-glucose index (TyG index), TyGindex with body mass index (TyG-BMI), TyG index with waist circumference (TyG-WC), and metabolic score for insulin resistance (METS-IR), are the most common of these less complicated and practical markers [19,20]. Although prior studies have shown associations between these indices and CAD, there is no speci c threshold for utilizing these indices, and it remains uncertain which one of them better predicts CAD [21][22][23].…”
Section: Introductionmentioning
confidence: 99%